Numerical study of turbulent heat transfer of nanofluids containing eco-friendly treated carbon nanotubes through a concentric annular heat exchanger. (December 2018) - Hosseini, Maryam; Abdelrazek, Ali H.; Sadri, Rad; Mallah, A.R.; Kazi, S.N.; Chew, B.T.; Rozali, Shaifulazuar; Yusoff, Nukman
Graphical abstract: Highlights: Eco-friendly treated-MWCNT nanofluids employed in simulation of convective heat transfer. Turbulent Single-phase flow with k - ω model was utilized to model nanofluid flow in 3D duct. The CFD results show good agreement with the experimental data and empirical correlations. By addition of nanoparticles in water the heat dissipation is improved. Abstract: In this study, we conducted numerical simulations using finite volume method to examine thermal and hydrodynamic characteristics of clove-treated multi-walled carbon nanotube (C-MWCNT)/distilled water nanofluids in a concentric annular heat exchanger exposed to uniform and constant heat flux boundary conditions. We devised an environmentally friendly functionalization method to synthesize the MWCNTs where the MWCNTs were covalently treated with clove buds in one pot using free radical grafting reaction for preparation of homogeneous MWCNT nanofluid without involving existing corrosive, hazardous acid based conventional functionalization methods of carbon nanomaterials. We analysed the C-MWCNTs using Fourier transform infrared spectroscopy in order to assess the surface modification of MWCNTs. Next, we performed numerical simulations in order to predict the convective heat transfer and hydrodynamic characteristics of the nanofluids considering three concentrations of C-MWCNTs: 0.075, 0.125, and 0.175 wt.%. The effective thermo-physical properties of the nanofluids, which we obtained experimentally, were used in our three-dimensional simulations in order to solve the governing equations of fluid dynamics (continuity, momentum and energy), along with the k - ω turbulence model. We found that there is a good agreement between the simulation and experimental results. We also noticed that the addition of a small fraction of C-MWCNTs into distilled water significantly enhances the convective heat transfer coefficient relative to distilled water. Our results are also encouraging because we observed that the friction factor does not vary significantly for the nanofluids at their concentration range. In general, we conclude that our simulation model can be used to predict the convective heat transfer and hydrodynamic characteristics of C-MWCNT/distilled water nanofluids in a concentric annular heat exchanger with reasonable accuracy and the results show the promising capabilities of these nanofluids as coolants.